Hereditary disease widespread in Syria - Nature Research (16552612) (2015)
The first study to determine the prevalence of congenital adrenal hyperplasia in Syria suggests that a mandatory screening programme is needed because of a lack of awareness about the condition. Congenital adrenal hyperplasia (CAH) is an inherited metabolic disorder in which mutations in genes encoding enzymes lead to dysregulation in production of the sex hormone androgen. Symptoms of the disease include cardiac arrhythmias, low blood pressure, genital ambiguity and sometimes death. It is thought to be highly prevalent in Syria because of the high rates of consanguinity—or marriage between blood relatives—but there are no official statistics. To collect some baseline data, Lina Ibrahem Sheikh Alshabab of Damascus University and her colleagues secured access to computerized medical records at the Children’s Hospital of Damascus, and extracted all cases between January 2008 and December 2012 that included a presumptive or final diagnosis of congenital adrenal hyperplasia. They identified 89 confirmed cases within that four-year period, including 20 males, 66 females, and three of undetermined gender. Parental consanguinity was present in 59 of them, and 17 of them had been previously hospitalized with CAH-related symptoms such as repetitive vomiting and diarrhea. Crucially, only 27 of the 89 confirmed cases were diagnosed with CAH within one month of birth, and genetic analyses further revealed that 32 of all cases were females who were misassigned as male at birth, reflecting the inability of healthcare staff to differentiate male genitalia from masculinized female genitalia. The researchers also identified 25 suspected cases. Seven of these were discharged early at their parent's request, and another seven died during the four-year period examined, but it's unclear if these were cases of CAH or if the deaths were caused by the condition. The findings suggest that CAH is relatively prevalent in Syria, and that there is an overall lack of awareness about the condition, especially among parents. The researchers suggest that a national mandatory screening programme would therefore improve diagnosis of CAH and reduce the number of deaths it causes, especially since nearly 70% of all cases were not identified during the first month of life. However, further research is needed, they add, to determine the cost-effectiveness of such a programme and whether it would be applicable in Syrian society. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0